ENGLISH LANGUAGE LEARNING MOTIVATION OF THAI STUDENTS OF LANTARATPRACHAUTIT SCHOOL - Fuji Puspita Damayanti; Dina Rachmawati (Eltin Journal : Journal of English Language Teaching in Indonesia, 2022)
Various factors influence students' motivation to learn a foreign language. As a country that has never been invaded by other countries and in which Thai is the official language and English is the only foreign language taught in schools, the study of students' motivation to learn English is worthwhile researching. The goal of this study was to find out what motivated students to learn English and how that desire manifested in classroom activities. Qualitative case study was employed in this study. Three data gathering procedures were used to acquire data i.e. questionnaire, observation, and semi-structured interview. To determine their motivation, 17 fifth-grade pupils at Lantaratprachautit School in Thailand were recruited to fill out a closed-ended questionnaire which was adapted from Gardner's Attitude/Motivation Test Battery (AMTB). Three students with varying levels of motivation were observed in order to determine how motivation was reflected in the English classroom. In addition, to triangulate the data in this study, a semi-structured interview was undertaken. The majority of the participants were assessed as having poor motivation, which was consistent with their classroom engagement. Finally, students' interest and participation in classroom activities in the English teaching-learning process represented their motivation in English language learning.